Upaya Meningkatkan Hasil Belajar Siswa Kelas V Mata Pelajaran IPAS Materi Magnet Melalui Model Problem Based Learning di UPT SDN 060800 Medan Area - Hasarah, Hasarah; Dwi, Dara Fitrah; Nurmairina, Nurmairina; Sihaloho, Effriana F. (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to analyze the impact of implementing the Problem-Based Learning (PBL) model on learning outcomes in Natural and Social Sciences (IPAS) on the subject of Magnetism in grade V at SDN Kuta Pasie with a total of 23 students. The study used a Classroom Action Research (CAR) approach conducted in two cycles. Data were collected through learning outcome tests in the form of pre-tests and post-tests, supplemented by observations of student activities and documentation of the learning process. Data analysis was conducted quantitatively by comparing pre-test and post-test scores using a paired t-test and calculating Cohen's d effect size to determine the strength of the effect. The results of the study show an increase in the average score from 38.3 on the pretest to 76.5 on the posttest, with an average difference of 38.3 points. Learning completeness increased from 1 student (4.3%) to 12 students (52.2%). The paired t-test produced a t-value of 7.190 with a Cohen's d effect size of 1.499, which is classified as large. These findings indicate that the application of the PBL model is effective in improving students' understanding of magnetic concepts while also encouraging an increase in learning completeness.